Perception of Repository Ease on Library Satisfaction at the UIN Raden Intan Lampung Library Using the TAM Model - INSANIA, INSANIA PUTRI; Zakky al-Hafizd, Muhammad; Nadila, Sinta (Jurnal El-Pustaka, 2025)
Digital libraries are the result of librarians' seriousness in providing maximum information services to all readers, hoping that the information available in libraries will provide maximum services to the wider community through digital information services. The purpose of this scientific article is to find out and examine the application of digital libraries in an effort to improve information services. Libraries as a supporting element in educational and teaching activities are currently carried out online and must adapt to the needs of their users. During this pandemic, digital libraries are increasingly in demand by the general public, especially users who are increasingly interested in studying and being scholars. The advantage of this digital library is that it can be accessed anywhere and anytime by users or users using the internet network to support operations and this system is considered the most suitable in the era of the millennial generation and can meet the need for information and library collections easily and at adequate speed. Based on the results of a review of several journals, it is stated that the implementation of digital library services is able to improve information services. With the existence of digital library services which are supported by comprehensive information quality factors, efficient service system quality, and service quality that meets user expectations. So that it can improve information services.